2004
DOI: 10.2207/qjjws.22.107
|View full text |Cite
|
Sign up to set email alerts
|

Low Transformation Temperaure Materials and Welding Residurl Stress-Application of the Laser Speckle Method to Strain Measurement in the Welding Process (Report 7)-

Abstract: Recently, materials with low transformation temperature have been investigated for improvement of reliability in welded joint. Due to the introduction of compressive residual stress by using the material, fatigue strength or resistance to cold cracking are improved. In this report the authors examined the effects of phase-transformational behavior on residual stress and their distribution using some basic models and some types of the behavior. Expansions and temperature range of phase-transformation detected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The M s point was clearly lower than the fixed beam result using LTTW O and the result of the strain change by the laser speckle method using LTTW B,R by Muramatsu. [25][26][27][28] O,B and R are one of LTTW. The M s point using LTTW was clearly lower in the fixed beam result than Muramatsu's result of the strain change using LTTW B,R measured by the laser speckle method.…”
Section: Influence Of Welding Condition (Welding Pass Sequence) On Re...mentioning
confidence: 99%
See 1 more Smart Citation
“…The M s point was clearly lower than the fixed beam result using LTTW O and the result of the strain change by the laser speckle method using LTTW B,R by Muramatsu. [25][26][27][28] O,B and R are one of LTTW. The M s point using LTTW was clearly lower in the fixed beam result than Muramatsu's result of the strain change using LTTW B,R measured by the laser speckle method.…”
Section: Influence Of Welding Condition (Welding Pass Sequence) On Re...mentioning
confidence: 99%
“…Furthermore, numerical calculations using the measurement results were carried out to estimate the residual stress. [25][26][27][28] However, a welded structure is different from a welded joint, and the shape of the welded joint or structural restraint influences the generation of residual stress, and so evaluation of welded structures is necessary. The boxing fillet welded joint was adopted as an example of a welded structure, and many papers have reported that the residual stress of the fillet corner region influences the fatigue strength.…”
Section: Introductionmentioning
confidence: 99%